Comparative of Conventional Marketing and Sharia Marketing Against Maslahah With Customer Satisfaction as Intervening at Customer Super Market in Batam City - Wibisono, Chabullah (Universitas Islam Negeri Alauddin Makassar, 2018)
The unbalanced development of modern markets and traditional markets, of course, as a result of conventional marketing and syariah marketing systems, has the effect of many current markets and the decline of traditional markets that are mostly owned by the economically weak communities in Batam, whether the impact of conventional maketing that make the city into behaving cosumtifically, it is necessary to conduct research